Stable solitary waves for one-dimensional Schrodinger-Poisson systems - Guoqing Zhang; Weiguo Zhang; Sanyang Liu (Electronic Journal of Differential Equations, 2016)
Based on the concentration compactness principle, we shoe the existence of ground state solitary wave solutions for one-dimensional Schrodinger-Poisson systems with large L2-norm in the energy space. We also obtain orbital stability for ground state solitary waves.